Potential Clinical Significance of Overall Targeting Accuracy and Motion Management in the Treatment of Tumors That Move With Respiration: Lessons Learnt From a Quarter Century of Stereotactic Body Radiotherapy From Dose Response Models - Mahadevan, Anand; Emami, Bahman; Grimm, Jimm; Kleinberg, Lawrence R.; Redmond, Kristin J.; Welsh, James S.; Rostock, Robert; Kemmerer, Eric; Forster, Kenneth M.; Stanford, Jason; Shah, Sunjay; Asbell, Sucha O.; et al. (Frontiers in Oncology, 2021)
Objective: To determine the long-term normal tissue complication probability with SBRT treatments for targets that move with respiration and its relation with the type of respiratory motion management (tracking vs. compression or gating). Methods: A PubMed search was performed for identifying literature regarding dose, volume, fractionation and toxicity (Grade 3 or higher) for SBRT treatments for tumors which move with respiration. From the identified papers logistic or probit dose-response models were fitted to the data using the maximum-likelihood technique and confidence intervals were based on the profile-likelihood method in the DVH Evaluator. Results: Pooled logistic and probit models for Grade 3 or higher toxicity for aorta, chest wall, duodenum and small bowel suggest a significant difference when live motion tracking was used for targeting tumors with move with respiration which was on the average 10 times lower, in the high dose range. Conclusion: Live respiratory motion management appears to have a better toxicity outcome when treating targets which move with respiration with very steep peripheral dose gradients. This analysis is however limited by sparsity of rigorous data due to poor reporting in the literature.